2021
DOI: 10.3758/s13415-021-00946-1
|View full text |Cite
|
Sign up to set email alerts
|

Better self-concept, better future choices? Behavioral and neural changes after a naturalistic self-concept training program for adolescents

Abstract: A large number of adolescents experience difficulty when choosing a suitable higher education program that matches their self-views. Stimulating self-concept development could help adolescents to increase their chances of finding a suitable major. We addressed this issue by examining the effects of a naturalistic self-concept training within a gap year context on behavioral and neural correlates of self-evaluations, as well as the long-term effects for future educational decision-making. In total, 38 adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…There is a dearth of studies with repeated measures of psychological problems and EA. Tollenaar et al (2021) found that internalizing symptoms during preschool significantly predicted EA at age 6 years, which was in turn significantly and prospectively associated with internalizing symptoms at ages 6-10 years. This study did not assess EA repeatedly, leaving it unclear whether changes in EA contribute to increasing problems, or vice versa.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…There is a dearth of studies with repeated measures of psychological problems and EA. Tollenaar et al (2021) found that internalizing symptoms during preschool significantly predicted EA at age 6 years, which was in turn significantly and prospectively associated with internalizing symptoms at ages 6-10 years. This study did not assess EA repeatedly, leaving it unclear whether changes in EA contribute to increasing problems, or vice versa.…”
Section: Introductionmentioning
confidence: 83%
“…Does EA during late adolescence predict changes in psychological problems? Extrapolating from extant research, we expected both EA during late adolescence and changes in EA from late adolescence to young adulthood to be positively associated with internalizing symptoms during young adulthood Smith et al, 2021;Tollenaar et al, 2021). Regarding externalizing problems, given inconsistent results showing either positive (Cicchetti & Handley, 2017; or no significant effects (Tollenaar et al, 2021), we kept the research question exploratory.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, the process-perspective on beliefs exemplified in the credition model does not yet seem to be wellrepresented in the ability estimate literature. While there is some work on the development and neural correlates of self-concepts (e.g., Chavez and Wagner, 2020;Van der Aar et al, 2022), we have yet to encounter an agreed-upon model on how people arrive at their assessments of their own and others' abilities. On the other hand, our work on ability estimates has highlighted the relevance of differentiating between ability domains and sources of estimates (i.e., the self and different types of others).…”
Section: Future Work On Ability Estimates and Beliefsmentioning
confidence: 99%